The Impact of Emotional Intelligence and Work–Life Balance on Organizational Commitment through the Mediation of Job Satisfaction among JNE Denpasar Couriers - I Ketut Setia Sapta; I Gede Aria Kusuma Putra; Nengah Landra; Gede Bayu Surya Parwita (International Journal of Economics, Commerce, and Management, 2025)
This study explores the impact of emotional intelligence and work–life balance on organizational commitment, with job satisfaction serving as a mediating variable, in the context of couriers at JNE Denpasar. Utilizing a quantitative research design, the study applies Partial Least Square (PLS) Structural Equation Modeling (SEM) to analyze data collected from 56 participants through a census sampling method. The findings reveal that emotional intelligence has a direct and significant effect on organizational commitment, indicating that employees with higher emotional intelligence tend to demonstrate stronger loyalty and dedication to their organization. However, emotional intelligence does not show a significant influence on job satisfaction, suggesting that other factors may contribute to employees' overall contentment at work. Conversely, work–life balance significantly affects job satisfaction, highlighting the importance of maintaining a healthy equilibrium between professional and personal responsibilities. Despite this, work–life balance does not directly influence organizational commitment. Further analysis indicates that job satisfaction fully mediates the relationship between work–life balance and organizational commitment, demonstrating that employees who achieve a better work–life balance are more likely to be satisfied with their jobs, which in turn enhances their commitment to the organization. However, job satisfaction does not serve as a mediator between emotional intelligence and organizational commitment, implying a more direct pathway between these two variables. These results align with the Theory of Planned Behavior, emphasizing that positive attitudes, reflected through job satisfaction, play a critical role in fostering behaviors associated with organizational commitment. From a practical perspective, the study highlights the importance for companies, particularly in the logistics industry, to invest in initiatives that enhance emotional intelligence and promote effective work–life balance strategies. By doing so, organizations can cultivate stronger employee loyalty, improve engagement, and foster a more committed workforce, ultimately contributing to better organizational performance and stability.